Evaluation of the knowledge, attitudes and practices of diabetic patients in a tertiary care hospital in Central India - Tejaswi, Prerna; Dhakre, S; Reddy, P; Goyal, C (International Journal of Medical Research and Review, 2018)
Introduction: A right approach to diabetes can reduce morbidity, mortality, and the burden of costs among diabetics. It is important to gather information about the knowledge, attitudes, and practices of people with diabetes to develop effective health education and diabetes control awareness programs. Objectives: To assess the knowledge, attitudes, and practices of patients suffering from type 2 diabetes. Materials and Methods: A prospective observational study was conducted with 100 type 2 diabetics of either gender, who were admitted in the general medicine ward and consented to participate in the study. A suitable 26-item semi-structured questionnaire was designed, with “Yes” and “No” as response options. Each appropriate answer was assigned a score of 1. Results: In total, 56%, 42%, and 2% of the subjects showed a good, moderate and poor knowledge grades, respectively. Regarding attitude, 64% and 36% of the patients exhibited good and poor grades, respectively. Only 31% of the participants achieved a good practice grade, 59% secured average while 10% of them got poor grades. The overall KAP results of 43% of the patients was good, 55% scored average whereas 2% scored poor grades. Assessment of the overall KAP grade with the demographic variables showed that there is a statistically significant association of the grades with the education, occupation, and socioeconomic status (P<0.05). Conclusion: It is necessary to provide appropriate health education and individual counseling to ensure that each patient with diabetes has sufficient information and that he/she is motivated to lead a better life.